Pre-colonization with the commensal fungus Candida albicans reduces murine susceptibility to Clostridium difficile infection. (2nd November 2018) - Markey, Laura; Shaban, Lamyaa; Green, Erin R.; Lemon, Katherine P.; Mecsas, Joan; Kumamoto, Carol A.
ABSTRACT: Clostridium difficile is a major nosocomial pathogen responsible for close to half a million infections and 27, 000 deaths annually in the U.S. Preceding antibiotic treatment is a major risk factor for C. difficile infection (CDI) leading to recognition that commensal microbes play a key role in resistance to CDI. Current antibiotic treatment of CDI is only partially successful due to a high rate of relapse. As a result, there is interest in understanding the effects of microbes on CDI susceptibility to support treatment of patients with probiotic microbes or entire microbial communities (e.g., fecal microbiota transplantation). The results reported here demonstrate that colonization with the human commensal fungus Candida albicans protects against lethal CDI in a murine model. Colonization with C. albicans did not increase the colonization resistance of the host. Rather, our findings showed that one effect of C. albicans colonization was to enhance a protective immune response. Mice pre-colonized with C. albicans expressed higher levels of IL-17A in infected tissue following C. difficile challenge compared to mice that were not colonized with C. albicans . Administration of cytokine IL-17A was demonstrated to be protective against lethal murine CDI in mice not colonized with C. albicans. C. albicans colonization was associated with changes in the abundance of some bacterial components of the gut microbiota. Therefore, C. albicans colonization altered the gut ecosystem, enhancing survival after C. difficile challenge. These findings demonstrate a new, beneficial role for C. albicans gut colonization.